Feminist Studies in the Context of Text-Based Criticism: "Woman as an Unpaid Worker" in Kishwar Naheed’s Essays - Malik, Sumaira (Makhz (Research Journal), 2024)
This paper explores the feminist critique of unpaid female labor as articulated in the essays of Kishwar Naheed, a pioneering feminist voice in South Asian literature. By applying text-based criticism to Naheed’s prose, the study foregrounds the systemic marginalization of women’s domestic and emotional labor, which remains economically invisible yet socially indispensable. Through a close reading of her essays, the analysis uncovers the ideological constructs that perpetuate gendered labor divisions in patriarchal societies, particularly in the cultural and political context of Pakistan. The paper situates Naheed’s arguments within the broader discourse of feminist political economy, drawing on theorists such as Silvia Federici and Angela Davis, to highlight the continuity between women’s oppression in the private sphere and their exclusion from formal labor narratives. Ultimately, the study demonstrates how taxt based criticism applies on Naheed’s essays serve as a potent form of resistance literature, challenging dominant narratives and advocating for the recognition of women’s unpaid labor as foundational to societal functioning.